2021
DOI: 10.3389/fmars.2021.651102
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Thresholds of Ocean Acidification Impacts on Decapods

Abstract: Assessing decapod sensitivity to regional-scale ocean acidification (OA) conditions is limited because of a fragmented understanding of the thresholds at which they exhibit biological response. To address this need, we undertook a three-step data synthesis: first, we compiled a dataset composed of 27,000 datapoints from 55 studies of decapod responses to OA. Second, we used statistical threshold analyses to identify OA thresholds using pH as a proxy for 13 response pathways from physiology to behavior, growth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 122 publications
0
13
0
Order By: Relevance
“…To put these conditions in perspective, the review of Gazeau et al (2013) documented responses of adult and larval/juvenile shelled molluscs pH decreases of ≤0.4 units, and found that while adults showed few negative responses, larval stages were much more vulnerable to acidification stress. Recent review of acidification effects on crustacea (Bednaršek et al, 2021) found frequent negative effects on adults and larval/juvenile stages to pH reductions ≤ 0.4, and experiments on decapod larvae combining acidification and hypoxia (Tomasetti et al, 2021) have demonstrated potential for severe synergistic effects over short exposure time scales. For New Zealand taxa, Law et al (2018) found that acidification levels we show for the Firth approached deleterious levels for macroalgae (corallines), and early life stages of sea urchins, sand dollars, abalone and New Zealand Greenshell R mussels, which are grown in the large mussel farms in the Firth (Law et al, 2019).…”
Section: Implications For Coastal Resource Managementmentioning
confidence: 99%
“…To put these conditions in perspective, the review of Gazeau et al (2013) documented responses of adult and larval/juvenile shelled molluscs pH decreases of ≤0.4 units, and found that while adults showed few negative responses, larval stages were much more vulnerable to acidification stress. Recent review of acidification effects on crustacea (Bednaršek et al, 2021) found frequent negative effects on adults and larval/juvenile stages to pH reductions ≤ 0.4, and experiments on decapod larvae combining acidification and hypoxia (Tomasetti et al, 2021) have demonstrated potential for severe synergistic effects over short exposure time scales. For New Zealand taxa, Law et al (2018) found that acidification levels we show for the Firth approached deleterious levels for macroalgae (corallines), and early life stages of sea urchins, sand dollars, abalone and New Zealand Greenshell R mussels, which are grown in the large mussel farms in the Firth (Law et al, 2019).…”
Section: Implications For Coastal Resource Managementmentioning
confidence: 99%
“…Recent meta-analyses on other physiological and life history traits (growth, fecundity, hatching success, and respiration) in decapod crustaceans confirm this difference between acute and chronic acclimation and strongly suggest that prolonged exposure to ocean acidification conditions further exacerbates negative physiological effects (Bednaršek et al, 2021). Definition of organismic responses at the acute versus chronic levels to climate change of any magnitude will require future studies to use physiologically and ecologically relevant timescales for their exposures.…”
Section: Application Of Our Results In These Experiments Is Particula...mentioning
confidence: 99%
“…Functional differences between crustacean exoskeletons could arise from divergent absolute levels of Ca 2+ , Mg 2+ , and their ratio. Other foci important in understanding the mechanisms of ocean acidification-mediated changes in exoskeletal properties include structural changes in the orientation of crystals within the mineralized layer (Chen et al, 2008;Rosen et al, 2020) and characterization of mineral deposition versus dissolution rates (Bednaršek et al, 2021), facets we did not assess in this study.…”
Section: Meta-analysis: Ion Content and Biomechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coastal areas are also more threatened by the increase in seawater temperature as they warm faster than open ocean (Hoegh-Guldberg et al, 2014;Fox-Kemper et al, 2021). The reductions in seawater pH and increases in seawater temperature can have deleterious effects on many coastal species, especially during earlier life-stages, which are often more sensitive than adult conspecifics (Kurihara, 2008;Ceballos-Osuna et al, 2013;Bednarsěk et al, 2021). Crustaceans are especially sensitive to those changes.…”
Section: Introductionmentioning
confidence: 99%